German Folktales as Interactive Teaching Strategies: Enhancing History and Culture Instruction Competence among German Teachers in Malang - Syafruddin, Dudy; Ardiyani, Dewi Kartika; Kharis, M.; Ratnasari, Dewi (Innovative Journal of Community Engagement, 2025)
The teaching of German as a foreign language requires the integration of cultural and historical content to foster intercultural competence. However, an implementation gap often exists, where teachers recognize the value of materials like folktales (Märchen) but lack the pedagogical strategies to use them beyond superficial storytelling. This community service project aimed to bridge this gap by designing, implementing, and evaluating a workshop to enhance German teachers' competence in using folktales for critical history and culture instruction. The program engaged 12 German teachers from Malang, Indonesia. It followed a structured four-phase coaching model: (1) needs analysis via a Likert-scale questionnaire; (2) design of a multidisciplinary curriculum featuring curated folktales (Hänsel und Gretel, Hans im Glück, Die Sterntaler); (3) implementation through modeling, guided practice, and lesson plan development; and (4) evaluation using post-workshop questionnaires and qualitative feedback. Post-workshop evaluation revealed significant outcomes. Quantitatively, 92% of participants reported enhanced understanding of the historical-cultural dimensions of folktales, while 67% to 83.3% showed improved self-efficacy in designing and implementing folktale-based lessons. Qualitatively, the workshop catalyzed a paradigm shift, with teachers transforming folktales from entertainment into artifacts for critical cultural analysis (e.g., examining feudalism and the Great Famine). Crucially, the emergence of teacher agency was evidenced by requests for advanced workshops and exploration of deeper literary texts, indicating sustainable impact. The workshop proved highly effective in transforming teacher competence and confidence. The synergy of coaching, multidisciplinary content, and a focus on agency not only closed the implementation gap but also laid the foundation for a sustainable community of critical practitioners in German language education in Indonesia.